THE INFLUENCE OF CORPORATE SOCIAL RESPONSIBILITY, BRAND PERSONALITY AND CORPORATE REPUTATION ON BRAND LOYALTY OF MODERN RETAILERS - Putra, Arie Pratama; Armanu, Armanu; Sudjatno, Sudjatno (Jurnal Aplikasi Manajemen, 2019)
This study aims to empirically examine the influence of corporate social responsibility (CSR) on brand loyalty with the brand personality and the corporate reputation as the mediators. This study used Partial Least Square (PLS) to analyze the data. The data was obtained from a survey by using the questionnaire with consumers of retail stores in Malang as its population. The samples were 150 visitors obtained by using non-probability sampling with purposive sampling technique. The findings of this study indicated that corporate social responsibility, either directly or indirectly, affected the brand loyalty through the mediation of the brand personality and corporate reputation. This study suggested the modern retailers pay more attention to the CSR program owned by their consumers. It highlighted the importance of improving the retailers’ corporate reputation and brand personality to be felt consumers to increase the retailers brand loyalty.